Employees’ fit to telework and work well-being: (in)voluntariness in telework as a mediating variable? - Lopes, Sílvia (2022)
Purpose: The present study aims to examine the mediating role of (in)voluntariness in teleworking in explaining the relationship between employees’ fit to telework and work well-being (i.e. work engagement and exhaustion). Design/methodology/approach: A cross-sectional survey design was used in this study. The sample comprised 222 individuals performing telework in Portugal. Statistical analyses employed were descriptive statistics, Pearson’s correlation, confirmatory factor and structural equation analyses, and mediation analysis using Hayes Process macro. Findings: The findings confirmed the hypothesis that employees’ fit to telework raises the voluntariness in telework and decreases involuntariness in telework. However, contrary to expectations, no significant relationships were found between voluntariness in telework, work engagement and exhaustion. Yet, involuntariness in telework showed a significant role in decreasing work engagement and increasing workers’ exhaustion. The mediating role of involuntariness in telework was confirmed in explaining the relationship between employees’ fit to telework and exhaustion. Practical implications: Managers in global firms can draw from the results to understand how employees’ fit to telework directly and/or indirectly contributes to work well-being and develop human resource (HR) management practices aiming to increase employees’ fit to telework. Originality/value: Although teleworking is already studied, to the best of the authors’ knowledge, no studies have analyzed the same conceptual model employees’ fit to telework, (in)voluntariness in teleworking and work well-being.